2011
DOI: 10.1126/science.1212868
|View full text |Cite
|
Sign up to set email alerts
|

Host Proteasomal Degradation Generates Amino Acids Essential for Intracellular Bacterial Growth

Abstract: Legionella pneumophila proliferates in environmental amoeba and human cells within the Legionella-containing vacuole (LCV). The exported AnkB F-box effector of L. pneumophila is anchored into the LCV membrane by host-mediated farnesylation. Here, we report that host proteasomal degradation of Lys(48)-linked polyubiquitinated proteins, assembled on the LCV by AnkB, generates amino acids required for intracellular bacterial proliferation. The severe defect of the ankB null mutant in proliferation within amoeba a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
332
0
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(339 citation statements)
references
References 38 publications
5
332
0
2
Order By: Relevance
“…Importantly, Ap nutrient acquisition does not involve lysosomal of proteasome degradation; instead, a bacterial serine protease seems to be involved. Recently, it was shown that host proteasomal degradation generates amino acids essential for Legionella pneumophila growth (42). Thus, intracellular pathogens evolved diverse mechanisms to obtain required nutrients for replication.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Ap nutrient acquisition does not involve lysosomal of proteasome degradation; instead, a bacterial serine protease seems to be involved. Recently, it was shown that host proteasomal degradation generates amino acids essential for Legionella pneumophila growth (42). Thus, intracellular pathogens evolved diverse mechanisms to obtain required nutrients for replication.…”
Section: Discussionmentioning
confidence: 99%
“…AnkB is crucial for L. pneumophila to acquire nutrition as it locates to the LCV membrane and recruits K48-linked polyubiquitinated proteins, the degradation of which yields amino acids for the bacteria. 125 Another study showed that AnkB is also modified by Trim21-mediated K11-linked ubiquitination; however, this fails to change its stability. 126 LegU1 and LegAU13 are integrated into the host SCF E3 complex, with the former directly ubiquitinating BAT3, a host co-chaperone of Hsp70 that is implicated in ER stress modulation.…”
Section: Shigella Flexnerimentioning
confidence: 99%
“…1). Amino acids also play an important role as nutrients during growth within host cells (14,20,(27)(28)(29).…”
mentioning
confidence: 99%